Weblog Promotes ESL Learners’ Writing Autonomy - Foroutan, Maryam; Noordin, Nooreen; Hamzah, Mohd Sahandri Gani bin (Journal of language teaching and research, 2013)
Today, we observe widespread application of the internet, both synchronous and asynchronous communication, by educators in many worldwide classes. Weblog (blog or web log) can be one of the instructional and integral components for ESL instructors. By applying interview and observation, this study reports on ESL students' experience and perceptions in applying weblog throughout a semester in a writing class in Malaysia. Besides, this study examined the effect of using Weblog on students' writing autonomy. The findings revealed that students enjoyed the process of publishing their writings, and exchanging their experience in the weblog. Students also acknowledged weblog as a tool which provides more opportunities to publish their writing freely, extend their interaction with their peers outside the class setting, be able to publish and share interesting videos, have the chance to look for the appropriate materials in the World Wide Web (WWW) and check their sentences in the Google simultaneously. Students enjoyed some features in weblog which cannot be found in conventional modes of teaching and learning, such as experiencing unlimited time and place, more independency and freedom in publishing and exchanging comments. With the empirical data presented in this study, weblog can be applied as a suitable instructional tool to promote autonomy among language learners. Index Terms--ESL, computer-mediated communication (CMC), weblog, writing skills, autonomy, social interaction